2015
DOI: 10.1093/humupd/dmu064
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosis of human preimplantation embryo viability

Abstract: New algorithms are being created for embryo selection based on their developmental kinetics in culture, and the impact of factors such as patient etiology and treatment are being clarified. Potential links between morphokinetic data and embryo karyotype are being elucidated. The introduction of new molecular methods of determining embryo chromosomal complement is proving to be accurate and reproducible, with the future trending toward CGH arrays or next generation sequencing as a rapid and reliable means of an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
117
1
5

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 165 publications
(127 citation statements)
references
References 196 publications
4
117
1
5
Order By: Relevance
“…The analysis of the years 2004-2013 showed that (a) there has been a decrease in the mean number of the embryos transferred; (b) an increase in pregnancy rates per transfer; (c) an increase in implantation rates; (d) and a notable reduction in the BEmbryo Wastager ate, mostly due to a reduced denominator, i.e., fewer embryos transferred. These results reinforce previous observations that the majority of the oocytes harvested and the majority of embryos produced during IVF are chromosomally or genetically abnormal [44,45]. The time has come to strengthen and support research in methods to assess embryo competence for live birth before the transfer.…”
Section: Discussionsupporting
confidence: 84%
“…The analysis of the years 2004-2013 showed that (a) there has been a decrease in the mean number of the embryos transferred; (b) an increase in pregnancy rates per transfer; (c) an increase in implantation rates; (d) and a notable reduction in the BEmbryo Wastager ate, mostly due to a reduced denominator, i.e., fewer embryos transferred. These results reinforce previous observations that the majority of the oocytes harvested and the majority of embryos produced during IVF are chromosomally or genetically abnormal [44,45]. The time has come to strengthen and support research in methods to assess embryo competence for live birth before the transfer.…”
Section: Discussionsupporting
confidence: 84%
“…The centrosome, responsible for the subsequent spindle and microtubule development within the embryo, is derived from the sperm, hence men with significant impairment in spermatogenesis, and oligospermia, may be responsible for higher rates of aneuploidy (the gain or loss of whole chromosomes) within the subsequent embryo (209,339). However, the most common cause of embryo aneuploidy is related to female age as the oocyte has been in a stage of arrested meiotic development in prophase since early fetal life, hence as a woman ages and is exposed to reactive oxygen species within the environment, there is a progressive loss of cohesion molecules that hold sister chromatids together, the incidence of aneuploidy increases exponentially (114), particularly the chiasmata proximal to the telomere (208). This is exacerbated by deterioration in cytoplasmic mitochondria and mRNA stores (369).…”
Section: Embryonic Developmentmentioning
confidence: 99%
“…However, individual laboratories will have differing culture systems, hence may have different findings, although the staging system proposed by Meseguer is one of the most widely used (216). This group demonstrated that the most predictive parameters of embryo implantation potential were the time between division to two cells and division to three cells, the time between division to three cells and subsequent division to four cells, and the time of division to five cells (114,216). They also demonstrated that the abnormal features of uneven blastomere size at the two-cell stage and abrupt cell division to three or more cells, and multi-nucleation at the four-cell stage resulted in embryos that would not implant.…”
Section: Embryonic Developmentmentioning
confidence: 99%
See 2 more Smart Citations